MOLECULAR DOCKING AND ADME STUDIES OF STIGMASTEROL COMPOUNDS AS ANTI-BREAST CANCER - Amir, Nur Insani; Nurfadillah, Arafah; Miladiarsi, Miladiarsi; Irma, Ade; Wahdaniar, Wahdaniar (Indonesian Journal of Pure and Applied Chemistry, 2025)
Molecular docking studies of stigmasterol (test ligand) and estradiol (control ligand) against the ER-Î± receptor were performed using PyRx software. This study aims to determine the interaction between stigmasterol ligands and ER-Î± receptors by the molecular docking method using PyRx. The study results show that stigmasterol and estradiol have the same binding energy value of -7.3 kcal/mol. The stigmasterol compound could therefore be used as a candidate for breast cancer drugs.